Stagnasi Reformasi Administrasi (Studi Pada Program SIMPELAKU Disdukcapil di Desa Girijaya Kecamatan Cibinong Kabupaten Cianjur) - Maesaroh, Dede Resa (ANTASENA: Governance and Innovation Journal, 2023)
This study aims to determine the Simpelaku Program in the implementation of Population Administration management and find out what are the inhibiting and supporting factors for the implementation of the Simpelaku Program in Girijaya Village, Cibinong District, Cianjur Regency. The method used in this research is qualitative research methods, data collection techniques using interviews, observation, as well as documentation and source triangulation. The results show that the implementation of the Simpelaku Program in Girijaya Village, Cibinong District, Cianjur Regency has been going well, it is indicated by the Girijaya Village Government supporting the Simpelaku Program by directly assisting the community in using Simpelaku online services, Although there are still obstacles in the implementation of the Simpelaku Program, such as the people of Girijaya Village, many do not understand the use of digital services, and have not been able to take advantage of technology in the form of G edget or computer, Simpelaku Program Applications often experience technical problems.